2016
DOI: 10.1016/j.physletb.2016.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Single and double inclusive forward jet production at the LHC ats=7and 13 TeV

Abstract: We provide a description of the transverse momentum spectrum of single inclusive forward jets produced at the LHC, at the center-of-mass energies of 7 and 13 TeV, using the high energy factorization (HEF) framework. We subsequently study double inclusive forward jet production and, in particular, we calculate contributions to azimuthal angle distributions coming from double parton scattering. We also compare our results for double inclusive jet production to those obtained with the Pythia Monte Carlo generator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 62 publications
1
13
0
Order By: Relevance
“…However, the effect of the vacuum final-state parton shower on φ was studied in Ref. [67] and it was demonstrated that the φ distributions obtained using the k T factorization and PYTHIA [68] with the final-state parton shower (FSR) agree in shape, while they differ slightly in normalization. When the FSR was neglected the two curves were almost on top of each other.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of the vacuum final-state parton shower on φ was studied in Ref. [67] and it was demonstrated that the φ distributions obtained using the k T factorization and PYTHIA [68] with the final-state parton shower (FSR) agree in shape, while they differ slightly in normalization. When the FSR was neglected the two curves were almost on top of each other.…”
Section: Discussionmentioning
confidence: 99%
“…Subtracting the latter evolution contribution from eq. (5.3) and rearranging the terms, one obtains the following expressions for subtracted one-loop corrections to both scattering vertices: 5) which are also free from log r-divergences. By similar reasoning, one can obtain the subtracted one-loop correction to the scattering vertex with any regularization for rapidity divergences, including one proposed in JHEP08(2020)055 ref.…”
Section: Jhep08(2020)055mentioning
confidence: 99%
“…This conclusion is likely to generalize on a wide class of observables which are sensitive to the transverse momentum of incoming partons and absent in the LO of CPM. The ∆φ-spectrum of a dijet or multi-jet system at small values of ∆φ (away from back-to-back configuration) is a good example of such an observable [4][5][6].…”
Section: Jhep08(2020)055mentioning
confidence: 99%
See 1 more Smart Citation
“…The parton densities x 1 f a/1 (x 1 , µ 2 ) are standard collinear parton densities and in our calculations we use CTEQ10NLO parton densities. The matrix elements |M g * g→g | 2 , |M g * q(q)→q(q) | 2 can be found in [28].…”
Section: Rapidity Dependence Of Average Transverse Momentummentioning
confidence: 99%